Fundamentals of applied electromagnetics - Ulaby, Fawwaz T. (Pearson, 2015)
This text bridges the gap between circuits and new electromagnetics material. This book begins coverage with transmission lines, leading students from familiar concepts into more advanced topics and applications. A user-friendly approach, full-color figures and images, and a set of interactive simulations will help readers understand the concepts presented.